2003
DOI: 10.1002/jmri.10319
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated dynamic MR imaging with a parallel imaging technique for hypervascular hepatocellular carcinomas: Usefulness of a test bolus in examination and subtraction imaging

Abstract: Purpose:To assess the impact of the accelerated dynamic MR imaging (ADMRI) approach using parallel imaging for detecting hypervascular hepatocellular carcinomas (HCCs) and to evaluate the usefulness of a test bolus in examination and subtraction imaging in this setting. Materials and Methods:Thirty patients with 135 HCCs underwent ADMRI using a two-dimensional gradient-recalled echo sequence with parallel imaging. Seventeen patients were evaluated without a test bolus and 13 patients with a test bolus. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A 3D gradient-echo sequence and parallel acquisition techniques facilitate dynamic contrast-enhanced imaging of HCC [7][8][9][10][11][12]. Gadobenate dimeglumine has been found useful for liver MRI.…”
Section: Choi Et Almentioning
confidence: 99%
“…A 3D gradient-echo sequence and parallel acquisition techniques facilitate dynamic contrast-enhanced imaging of HCC [7][8][9][10][11][12]. Gadobenate dimeglumine has been found useful for liver MRI.…”
Section: Choi Et Almentioning
confidence: 99%
“…With the recent introduction of 3D T 1 -weighted imaging and parallel acquisition techniques for MRI, imaging acquisition time has been remarkably shortened and the z-axis spatial resolution has been improved [31][32][33] . The combined use of both techniques allows acquisition of dynamic liver MR images with double arterial phases and thinner sections, thereby improving the detection of hypervascular HCCs [34] . Indeed, in previous studies by Kim et al [24,25] and Bhartia et al [35] , nearly the same temporal (double arterial phases) and spatial (slice thickness: 2.5-4 mm) resolution could be used in both MDCT (slice thickness: 3 mm) and MRI (slice thickness: 2.5-4 mm), explaining the superiority of MDCT and Gd-enhanced 3D T 1 -weighted MRI in detecting HCC compared to SDCT.…”
Section: Difficulties In Analyzing Performances Of Radiologic Modalitmentioning
confidence: 99%
“…SENSE, which is one parallel imaging method, permits considerable scan-time reduction with respect to standard Fourier imaging [9]. Prior reports described that multiple arterial phases, acquired using higher temporal-resolution dynamic MRI with parallel imaging, improved the sensitivity for detecting HCC [15][16][17][18]. Other studies reported that higher-spatial-resolution MR imaging using parallel imaging resulted in high image quality with shorter acquisition times on T2-weighted sequences [19].…”
Section: Discussionmentioning
confidence: 96%